2020
DOI: 10.1063/5.0010080
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of secondary electron emission effect on the dusty plasma sheath with superextensive electrons

Abstract: We have investigated the structure of a magnetized sheath of dusty plasma in the presence of secondary electrons emitted by the micro-size dust particles in the context of the Tsallis statistics. The fluid model is used to analyze numerically the effects of the nonextensivity parameter q on the emission of secondary electrons and therefore, on the sheath structure as well as the dust dynamics. The results show that the secondary emission yield increases with the decrease of the parameter of nonextensivity q an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The collection of the electron current, I e , for the q-distribution is given as. [6,9] I e = −en e 𝜋r…”
Section: Theoretical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The collection of the electron current, I e , for the q-distribution is given as. [6,9] I e = −en e 𝜋r…”
Section: Theoretical Modelmentioning
confidence: 99%
“…$$ [ 14 ] Since the SEE including the BEE, IRE and TEE plays an important role on the dust particle potential and then modifies the dust particle lifetime, it is necessary to investigate the impact of SEE on the dust particle in a plasma with super‐extensive electrons, because the presence of the super‐extensive electrons can have enough energy and then eject the secondary electrons from a dust particle producing a SEE current. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study shows that the critical SSE coefficient (Îłc$$ {\gamma}_c $$) increases for the super‐extensive distribution of electrons (q<1$$ q<1 $$) while it decreases for the sub‐extensive electron distribution (q>1$$ q>1 $$). Ghani et al [ 32 ] investigated the effect of SEE on a dusty plasma sheath and reported that the secondary emission yield increases with the decrease in q$$ q $$ and consequently observed a reduction in the dust charge. Exploring such problems by incorporating collisional effects will bring new insight to the problem.…”
Section: Introductionmentioning
confidence: 99%